Collaboration Model between PTKI and DUDI for Quality and Equality in Education 2045 - Pepilina, Dini; Fauzi, Fauzi; Aunillah, M. Zulfikar Sulkhi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to formulate a strategic collaboration model between Islamic Higher Education Institutions (PTKI) and the Business and Industrial Sector (DUDI) to improve the quality and equity of education toward Indonesia’s Golden Vision 2045. This research employs a library research design with a descriptive qualitative approach by analyzing 20 selected scientific articles, academic books, and policy documents published between 2021 and 2025. The data were collected through literature screening and purposive selection based on thematic relevance to PTKI–industry collaboration. Data analysis used content analysis to identify patterns, themes, and conceptual linkages. The findings show that PTKI–DUDI collaboration can be implemented through joint curriculum development, structured internships, research collaboration, entrepreneurship incubation, digital learning expansion for 3T regions, scholarship provision, and talent recruitment. This collaboration not only strengthens graduates’ employability but also promotes equitable access to high-quality education while maintaining the values of moderate Islam. Therefore, the PTKI–DUDI collaboration model has significant potential as a strategic instrument to support the Sustainable Development Goals and Indonesia Emas 2045.